Islam dan Demokrasi di Pakistan - Wulandari, Fitri (El Tarikh : Journal of History, Culture and Islamic Civilization, 2021)
Pakistan is an Islamic country with the third largest Muslim population in the world. However, the size of the Muslims here is inversely proportional to the recognition of Pakistan as an insecure and conflict-prone country. In fact, the use of Islam as the state ideology is not always easy in implementing Islamic law perfectly. Islam, which is manifested as an ideology in its elaboration, has not yet reached a national consensus, especially to find a common ground between Islam and democracy. This journal writing aims to examine more deeply the application of Islam and democracy in Pakistan. To approach the problem, this study uses a political sociology approach by referring to the theory put forward by John L. Esposito and James P. Piscatory. Collecting data in this study using techniques library research, while in the analysis using qualitative sources and other supporting sources. This research results in the finding that there is a mutually interesting relationship between Islam and democracy in government in Pakistan. This occurs because of differences in views between Islamic groups in interpreting Islam as the state ideology. This difference is what causes the application of Islamic law to not necessarily coincide with democratic practices in Pakistan.